Biodegradation of Carbon Nanotubes by Macrophages - Yang, Mei; Zhang, Minfang (Frontiers in Materials, 2019)
Carbon nanotubes (CNTs) are considered to be among the most promising materials of the 21st century due to their electronic, optical, mechanical, and thermodynamic properties. As the projected use of CNTs has increased in a variety of fields, including nanoelectronics, energy, materials science, and biology, their long-term toxicity has attracted increasing concern. This issue is especially important because CNTs are extremely physically and chemically stable, and therefore may not be biodegradable. However, novel approaches for degrading CNTs have been developed. These methods, which use peroxidases, neutrophils, and macrophages in vitro and in vivo, have yielded some encouraging results. In this minireview, we summarize current research on the biodegradation of CNTs, in particular by macrophages. We also discuss the factors that influence the biodegradation of CNTs according to their individual characteristics, with the aim of facilitating their applications.